METAPHOR ANALYSIS IN THE HIKAYAT SI MISKIN AS CLASSICAL MALAY LITERATURE - Subagiharti, Heni; Handayani, Diah Syafitri (University of Kuningan, 2025)
Hikayat Si Miskin is one of the classical Malay literary works that is rich in cultural and moral values. In this work, the use of metaphors is one of the main tools to convey symbolic messages and enrich the aesthetics of the story. This study aims to analyze the metaphors contained in Hikayat Si Miskin using a semiotic approach and classical literary studies. This study found that the metaphors in this text function to describe the social struggle, religiosity, and dynamics of the main character's life. For example,